LEXICOGRAPHICAL FIXATION OF BLENDS AND OXYMORONYMS (Proceedings of Southern Federal University. Philology, 2012)
Korobkina N.I.Keywords: contextual notion, blend, oxymoronym, dictionary (lexicographical source), dictionary entry, lema, linguistic informational domain, encyclopaedic informational domain.The article explains topicality of contemporary lexicographical research within the theory of the language. The author differentiates the notions “blend” and “oxymoronym” and defined the essence of the term “contextual notion”. The necessity of lexicographical fixation of such neologisms via creating a new lingual encyclopaedic dictionary is justified as it performs a recoding and prescribing function. The article gives examples of potential dictionary entries, consisting of linguistic and encyclopaedic informational domains and a list of conventional abbreviations used in them.